2022
DOI: 10.1158/1078-0432.ccr-22-1206
|View full text |Cite
|
Sign up to set email alerts
|

Gene-Expression Profiling of Mucinous Ovarian Tumors and Comparison with Upper and Lower Gastrointestinal Tumors Identifies Markers Associated with Adverse Outcomes

Abstract: Purpose: Advanced stage MOC have poor chemotherapy response and prognosis and lack biomarkers to aid Stage I adjuvant treatment. Differentiating primary mucinous ovarian carcinoma (MOC) from gastrointestinal (GI) metastases to the ovary is also challenging due to phenotypic similarities. Clinicopathological and gene expression data were analysed to identify prognostic and diagnostic features. Experimental Design: Discovery analyses selected 19 genes with prognostic/diagnostic potential. Validation was performe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 50 publications
2
26
0
Order By: Relevance
“…Some retrospective analyses have suggested improvement in outcomes with gastrointestinal regimens [67], though these are no substitute for prospective randomised studies. While ERBB2 has been identified as a potential target for therapeutic interventions, recent analysis suggests this event most frequently occurs in early stage MOC, with an amplification rate of only ~15% in stage III/IV MOC [64]. This study also identified higher ERBB2 expression in expansile versus infiltrative MOC.…”
Section: Mucinous Ovarian Carcinomasupporting
confidence: 48%
See 2 more Smart Citations
“…Some retrospective analyses have suggested improvement in outcomes with gastrointestinal regimens [67], though these are no substitute for prospective randomised studies. While ERBB2 has been identified as a potential target for therapeutic interventions, recent analysis suggests this event most frequently occurs in early stage MOC, with an amplification rate of only ~15% in stage III/IV MOC [64]. This study also identified higher ERBB2 expression in expansile versus infiltrative MOC.…”
Section: Mucinous Ovarian Carcinomasupporting
confidence: 48%
“…These Mullerian type cases were reclassified as a distinct entity termed 'seromucinous' over the last decade, displaying a distinct PAX8-positive and ER-positive immunoprofile (true MOC are PAX8 negative and almost always ER negative), and have since been further reclassified to reflect their recent recognition as variants of EnOC [63]. Recently, subclassification of MOC into expansile (~80% of cases) versus infiltrative invasive types (~20% of cases) has revealed poorer survival within the infiltrative invasive type [64,65].…”
Section: Mucinous Ovarian Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…There may be a difference between subtypes of mucinous cancer such as endocervical or gastrointestinal which contribute to these findings, although these data were not available for our cases [ 29 , 30 ]. Our study adds to the scant literature on the relationship between ciliated cells and the origin of mucinous EOC in contrast to the origin of other EOC histologic subtypes [ 31 ].…”
Section: Discussionmentioning
confidence: 87%
“…Similarly tumors with an infiltrative pattern of invasion had higher tumor epithelial PD-1+ cells, and higher stromal FOXP3+ Tregs. An infiltrative pattern of invasion is associated with a poorer prognosis [13], potentially involving an environment of T cell exhaustion/suppression. We showed on univariate analysis only that high epithelial density of FOXP3+ cells was associated with poorer overall survival.…”
Section: Discussionmentioning
confidence: 99%